Management of the Banana Bunchy Top Virus, lessons and tools - Omondi, Bonaventure Aman (2024)
The banana bunchy top disease (BBTD) is an invasive disease of Musa spp (banana and plantain), presently spreading in Africa. This spread threatens both banana production and safety of germplasm conserved on farm as farmer landraces in the two centres of secondary expansion, East African Highland Bananas (Great Lakes Region) and Plantain (West Africa). The Banana Bunchy top Virus (BBTV) is spread by the banana aphid, Pentalonia nigronervosa; and the sister species P. caladii, and by planting infected planting material. Yet, the control has previously focused more on the seed systems, exclusion, virus diagnostics, digital and spatial mapping tools and most recently recovery of production through roguing. Understanding the role of vectors may open additional control options. Vector manipulation presents a possible dimension of BBTD management, and so its contribution to integrated disease control has been limited to recent studies on botanical products. Studies to show virus and vector host spectrum, behaviour and phenomics are important to support landscape approaches to BBTD control. Understanding vector phenomics will help identify risk factors within a production year. An investigation of tritrophic interactions in the BBTD system suggests an element of vector manipulation; that could support minimizing disease risk if understood. Finally unravelling vector interactions with plant chemical signals may support the development of disease minimization approaches to protect seed and production farms. We present some findings in these areas and discuss the role of such studies in managing BBTD risk in various landscapes in Africa.